3DS MAX 4 in Depth. - McFarland, Jon
Provides readers with a comprehensive reference for creating effects for film, movies, and games. This book covers the modeling and modification of structures from primitive objects, plus other parametric design tools found in the program. and contains various projects to strengthen concepts learned with a color studio to showcase the results. CD-ROM is included with maps or clips needed for each exercise.